2017
DOI: 10.1016/j.scitotenv.2017.02.224
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a microalgal photobioreactor treating toilet wastewater: Pharmaceutically active compound removal and biomass harvesting

Abstract: In this study, a 1200L outdoor pilot scale microalgal photobioreactor (PBR) was used for toilet wastewater (WW) treatment and evaluate its ability to remove pharmaceutically active compounds (PhACs). The PBR was operated at two different hydraulic retention times (HRTs), which were 8 and 12days, during Period I (September-October) and Period II (October-December), respectively. Algal biomass concentrations varied by operating period because of seasonal changes. Nutrients (ammonia, nitrogen and total phosphorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(60 citation statements)
references
References 95 publications
4
55
0
1
Order By: Relevance
“…Interest in microalgae-based wastewater treatment has increased in recent years since, while growing, these microorganisms are able to uptake pollutants like nutrients [6] and trace metals [7], but also emerging contaminants (ECs) such as pharmaceuticals [8][9][10]. The latter represent an especially worrying class of contaminants since they were designed to provoke a physiological response and their presence in the aquatic environment may affect non-target individuals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest in microalgae-based wastewater treatment has increased in recent years since, while growing, these microorganisms are able to uptake pollutants like nutrients [6] and trace metals [7], but also emerging contaminants (ECs) such as pharmaceuticals [8][9][10]. The latter represent an especially worrying class of contaminants since they were designed to provoke a physiological response and their presence in the aquatic environment may affect non-target individuals.…”
Section: Introductionmentioning
confidence: 99%
“…The latter represent an especially worrying class of contaminants since they were designed to provoke a physiological response and their presence in the aquatic environment may affect non-target individuals. Among the different treatments proposed for the removal of pharmaceuticals from wastewater, microalgae-based systems have been proved to be effective either in close [8] or open [11] systems. Whatever the system configuration, biodegradation, together with bioadsorption and bioaccumulation, have been indicated as the main mechanisms for the removal of pharmaceuticals from wastewater [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hom-Diaz et al [177] observed that the removal of pharmaceuticals from domestic wastewater in a pilot-scale tubular photobioreactor, in two seasonal periods (September-October; October-December), was highly impacted by temperature and solar irradiation.…”
Section: Factors That Influence the Degradation Capabilitymentioning
confidence: 99%
“…Some algae strains found in the literature [64,133,148,164,166,[168][169][170][176][177][178][179][180][182][183][184][185][186][187][188][189][190][191][192][193][194] proved to be effective in pharmaceutical removal (Table 1). Laboratory-scale batch assays [190] Biodegradation Laboratory-scale batch assays [191] Salicylic acid or paracetamol Pharmaceutical industry wastewater Algae…”
Section: Concluding Remarks and Future Challengesmentioning
confidence: 99%
“…A comprehensive review by [67] shows that similarly to constructed wetlands, EC removal rate in HRAPs varies from insignificant to complete reduction. Also, results from studies conducted in closed algae reactors [94] indicate that removal efficiency of emerging contaminants depends on chemical properties of each substance individually, and is largely determined by treatment system scale, operational regime and design as well as climatic conditions. Thus, it can be concluded that the unpredictable and selective performance makes algae production rather unsuitable for emerging contamination reduction, and likewise is the applicability of AAFW.…”
Section: Emerging Contaminantsmentioning
confidence: 99%